A New RF Budget Analysis and RF Measurement Testbench Application - Kamislioglu, Bircan; Akbal, Ayhan (Ieee, 2018)
This paper presents RF systems that provide a more flexible and soft design work flow than traditional methods and uses in modeling and simulating. RF systems must include that efficient use of available spectrum, higher data rates and lower latency and lower power consumption. In addition, these requirements, advances in device integration are causing RF front ends to become highly complex, adaptive systems. This explain us RF system design is no longer performed in isolation. RF system that combined modeling and simulation environment obtains design with faster and fewer errors, which convert competitive advantages immediately.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: RF; modeling; simulating; 5G